The influence of the 5E learning cycle model assisted by the solar system scope application on student learning outcomes - St. Humaerah Syarif; Evi Puspitasari Rahman (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2025)
It is a chance for students to build their knowledge and experience through meaningfully engaging with the material. The goals of the study are (1) to assess the impact of the 5E learning cycle model supported by the solar system scope application on student learning results and (2) to assess the impact of the 5E learning cycle model supported by the solar system scope application on student learning results. The research type is a pseudo-experiment. The research design follows a nonequivalent control group framework, and the sample selection is conducted through purposive sampling. The study occurred at MTsN Pinrang, involving class VII students from 8 classes totaling 147 students, with class VII.1 having 20 individuals as the control group and class VII.2 having 20 individuals as the experimental group. The data collection methods include assessments for learning outcomes and non-test methods in the form of observation sheets for student activity and learning execution. Data analysis techniques involve both descriptive and inferential statistical assessments. The findings of this study indicate that (1) the 5E learning cycle model supported by the solar system scope application affects students' learning outcomes. This conclusion is drawn from hypothesis testing using an independent sample t-test, which reveals a p-value (2-tailed) of 0.000 < 0.05 and (2) the effect of the 5E learning cycle model supported by the solar system scope application on student learning outcomes, as demonstrated by Cohen's d effect size test, is 1.64, indicating a relatively high effect with a percentage of 94.5%.